Unraveling the Sexual Victimization of Sex Workers: A Latent Class Analysis Through the Lens of Environmental Criminology - Miin Miin Chai, April (Crime & delinquency, 2025)
Past research on violence against sex workers has contributed to our understanding of this phenomenon yet, often do not offer concrete preventative measures. The current study aims to investigate this issue through an environmental criminology perspective, and to identify measures that can be implemented to decrease violence through a situational crime prevention framework. Our sample consist of 402 French sex workers who experienced violent victimization (1990?2018). Latent class analysis revealed a four-class solution: (1) indoor/low-moderate guardianship, (2) outdoor/low guardianship, (3) mobile/low guardianship, and (4) mobile/moderate guardianship. Actionable crime prevention methods to mitigate the risk of violence suggested for each of the classes included pre-screening clients, installing panic buttons/closed-circuit television, offering self-defense and conflict management courses, and working in tandem.